Penyelesaian Tindak Pidana Ringan Melalui Upaya Nonpenal - Deni Pramono; Slamet Rohadi; Galuh Adi Wijaya; Andreas Zulkarnain (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2023)
This study of analyze the settlement of minor crimes through the non penal route as well as efforts to overcome obstacles and sanctions given in the settlement of minor crimes through the non-penal route. The approach used is the statute approach, the analytical approach and the conceptual approach, the case approach. The types and sources of legal materials are primary legal materials, secondary legal materials. The technique of collecting legal materials in normative research is known as library research, namely the technique of collecting legal materials between primary, secondary and tertiary legal materials. Legal material analysis techniques in this study used descriptive-evaluative legal material analysis techniques and interpretive analysis. The results of his research are as written in Article 18 paragraph (1) of Law Number 2 of 2002 concerning the State Police "for the public and community interests, officials of the Indonesian National Police in carrying out their functions, duties and authorities can act in accordance with their own evaluators. Paragraph (2) stipulates that the implementation of the provisions referred to in paragraph (1) can only be carried out in very necessary circumstances with due observance of laws and regulations, as well as the Code of Ethics of the Indonesian National Police.